Albumin Use in Patients With Cirrhosis in France: Results of the "ALBU-LIVE" Survey. Issue 9 (October 2017) - Garioud, Armand; Cadranel, Jean-François; Pauwels, Arnaud; Nousbaum, Jean-Baptiste; Thévenot, Thierry; Dao, Thong; Louvet, Alexandre; Sogni, Philippe; Talbodec, Nathalie; Antonini, Teresa M.; Bureau, Christophe; Thabut, Dominique; et al.
Abstract : Introduction: The use of human albumin for the management of cirrhosis has increased. Recommendations have been published for therapeutic paracentesis (TP), spontaneous bacterial peritonitis (SBP), and type 1 hepatorenal syndrome (HRS). The goal of this survey was to assess the prescription practices of French hepatogastroenterologists. Methods: All hepatogastroenterologists were contacted. The questionnaire evaluated (1) the use of albumin in validated indications and (2) the prescription of albumin for nonvalidated clinical situations. Results: Responses were analyzed from 451 (50.1%) practitioners. The mean age was 40 years (range, 24 to 67 y). Physicians practiced in a university hospital (47.7%) or a general hospital (45.8%). There were 56.7% senior practitioners. Overall 99.6% of the practitioners compensated for TP. Albumin was used by 87.8% of the physicians, with a fixed dose being used by 84.6%. For SBP, 94% of the physicians used albumin concomitantly with antibiotics. The recommended protocol was followed by 56.2% of the practitioners: more often by senior university hospital practitioners than by senior general hospital practitioners ( P =0.015). About 66.5% used albumin infusion for the diagnosis of HRS: used more often by senior university hospital practitioners ( P =0.0006). Albumin was used concomitantly with vasopressor treatment by 84%; the dose and the duration varied considerably. About 23.5% used albumin for severe bacterial infection, 47.9% for severe hyponatremia, 43.9% for severe hypoalbuminemia, and 65.9% for hydrothorax. Conclusions: In this large French survey, albumin is only prescribed in accordance with recommendations for TP. The schedule for SBP is followed by only 56% of the practitioners. The use of albumin for HRS is not adapted to recommendations, which are not well known, suggesting that they should be more diffused.